Arylpiperazine-containing pyrrole 3-carboxamide derivatives targeting serotonin 5-HT2A, 5-HT2C, and the serotonin transporter as a potential antidepressant - Kang, Suk Youn; Park, Eun-Jung; Park, Woo-Kyu; Kim, Hyun Jung; Jeong, Daeyoung; Jung, Myung Eun; Song, Kwang-Seop; Lee, Suk Ho; Seo, Hee Jeong; Kim, Min Ju; Lee, MinWoo; Han, Ho-Kyun; et al. (Pergamon Press Ltd., 2010)
Arylpiperzine-containing pyrrole 3-carboxamide derivatives were synthesized and evaluated as novel antidepressant compounds. The various analogues were efficiently prepared and bio-assayed for binding to 5-HT2A, 5-HT2C receptor, and 5-HT transporter. Based on their in vitro and in vivo activities as well as selectivity over other neurotransmitter receptors and PK profiles, 33 and 34 were identified as lead compounds. Consequently, this pyrrole series of compounds appears to be promising enough to warrant further investigation. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: RECEPTOR ANTAGONIST; UPTAKE INHIBITORS; DEPRESSION; NEFAZODONE; PINDOLOL; FLUOXETINE; LIGANDS; TRIAL